The Influence of Technological, Organizational and Environmental Factors on Accounting Information System Usage among Jordanian Small and Medium-sized Enterprises - Lutfi, Abd Alwali; Idris, Kamil Md; Mohamad, Rosli (International Journal of Economics and Financial Issues, 2016)
Accounting information plays a very crucial role in support of various business decisions. Widespread use of Information Technology (IT) enhances accounting functions to be more effective and efficient in supplementing accounting-related information. A computer-based accounting systems (Accounting Information System) enables more accurate reporting, processing large amount of transactions and produce more meaningful reporting for analysis. Despite the promised benefits of AIS, Small and Medium-sized Enterprises (SMEs) have been reported to be lagged behind on its use. Therefore, this study examines factors affecting the use of AIS amongst Jordanian SMEs based on Technology–Organization–Environment (TOE) framework. The study employed self-administered survey questionnaire as a mean of data collection. Based on the responses from 187 firms, compatibility, owner/manager commitment, organizational readiness, competitive pressure and government support were found to have significant effect on AIS usage among firms. This study confirms applicability of TOE framework in understanding factors affecting AIS usage in SMEs. Keywords: Usage Decision; Accounting Information System; Technology–Organization–Environment (TOE) Framework; Informal Networking JEL Classification: M400